El proceso metodológico en la enseñanza aprendizaje del futbol en los niños de 10 y 12 años de la escuela Enrique Mora Zares de la ciudad de Machala en el periodo lectivo 2013 - 2014. - Crespo Pineda, Bismark Manuel (2015)
The sport today it plans and so required the teacher , is consistent with current needs , the way in which we live there is a need for students to develop all the physical and technical abilities to whatever the discipline to practice , and is born from the need to improve .